SHARED KNOWLEDGE CONSTRUCTION IN VIRTUAL LEARNING ENVIRONMENTS IN BASIC EDUCATION STUDENTS - Villegas, Carmen Rosa Berrocal (2022)
The shared construction of knowledge is framed within the pedagogy of socio-constructivism. However, due to its incipient study, comprehension, and implementation, it presents certain characteristics that should be analyzed, even more so, in the context of the COVID-19 pandemic, which has conditioned an emergency non-face-to-face education supported by ICTs. In this sense, the present study aimed to analyze the shared construction of knowledge in virtual learning environments, in elementary education students of two governmental educational institutions in the district of Santa Anita, belonging to the Local Educational Management Unit 06, Lima-Peru. In a basic, quantitative, non-experimental, and comparative research, 260 students pertaining to the last three years of secondary education were evaluated through the application of an online questionnaire, which contemplated validity by expert judgment and reliability that indicates an excellent internal consistency. The obtained results show that there is a scarcely shared construction of knowledge through virtual learning environments. Likewise, there are no statistical differences in the shared construction of knowledge in Virtual Learning Environments according to the educational institutions of origin, as well as the grades of study. However, there are statistically significant differences in terms of gender.